The Influence of Communication and Work Environment on Employee Performance at the Regional Revenue Agency UPTD of Pandan Revenue Management - Nelly Bahria Napitupulu; Kaharuddin Kaharuddin; Rosmita Ambarita (Journal of Economics, Management and Accounting (JEMA), 2026)
This study aims to examine the influence of communication and work environment on employee performance at the UPTD Regional Revenue Management of Pandan. This research employs a quantitative method with a descriptive approach. The research sample consists of 58 employees of UPTD Regional Revenue Management of Pandan, who were selected as respondents through a questionnaire survey. The results show that the coefficient of determination (R²) is 0.608, indicating that 60.8% of the variation in employee performance can be explained jointly by communication and work environment, while the remaining 39.2% is influenced by other factors outside the scope of this study, such as leadership, competence, motivational incentives, and supervision. The t-test results reveal that communication has a positive and significant effect on employee performance, with a t-value of 3.476 > t-table 2.00404 and a significance of 0.001 < 0.05. Likewise, the work environment positively and significantly affects employee performance, with a t-value of 3.709 > t-table 2.00404 and a significance of 0.000 < 0.05. Furthermore, the F-test shows an F-value of 42.682 > F-table 3.16 with a significance of 0.000 < 0.05, indicating that communication and work environment simultaneously have a positive and significant effect on employee performance. Based on these findings, it is recommended that UPTD Regional Revenue Management of Pandan continue to enhance effective communication and create a conducive work environment to support the improvement of employee performance.